Mapping QTL for heat tolerance at flowering stage in rice using SNP markers - Ye, Changrong; Argayoso, May A.; Redoña, Edilberto D.; Sierra, Sheryl N.; Laza, Marcelino A.; Dilla, Christine J.; Mo, Youngjun; Thomson, Michael J.; Chin, Joong Hyoun; Delaviña, Celia B.; Diaz, Genaleen Q.; Hernandez, Jose E. (Wiley, 2012)
With 3 figures and 5 tablesTo identify quantitative trait loci (QTL) controlling heat tolerance in rice, the progeny of BC1F1 and F2 populations derived from an IR64 × N22 cross were exposed to 38/24°C for 14 days at the flowering stage, and spikelet fertility was assessed. A custom 384‐plex Illumina GoldenGate genotyping assay was used to genotype the F2 and selected BC1F1 plants. Four single nucleotide polymorphisms were associated with heat tolerance in the BC1F1 population using selective genotyping and single marker analysis, and four putative QTL were found to be associated with heat tolerance in the F2 population. Two major QTL were located on chromosome 1 (qHTSF1.1) and chromosome 4 (qHTSF4.1). These two major QTL could explain 12.6% (qHTSF1.1) and 17.6% (qHTSF4.1) of the variation in spikelet fertility under high temperature. Tolerant allele of qHTSF1.1 was from the susceptible parent IR64, and that of qHTSF4.1 was from tolerant parent N22. The effect of qHTSF4.1 on chromosome 4 was confirmed in selected BC2F2 progeny from the same IR64 × N22 cross, and the plants with qHTSF4.1 showed significantly higher spikelet fertility than other genotypes.